IMPROVING STUDENTS’ WRITING NARRATIVE TEXTS THROUGH EXPLORATION - EXPLANATION - EXPRESSION (E3) METHOD - Evi Nurhidayah (Institut Pendidikan Indonesia Garut, 2019)
This study which is entitled ‘’Improving Students’ Writing Narrative Text Through Exploration-Explanation-Expression (E3) Method’’. It aims to find out the effectiveness of Exploration-Explanation-Expression (E3) Method as a method in improving students’ ability in writing narrative text. The method used in this study was quantitative method. The design of this study was pre-experimental research design. The result showed that Exploration - Explanation - Expression (E3) Method is effective in improving students’ ability in writing narrative text. The result of calculation showed that in the significance degree of (ɑ) 0.05. The value of tobserved > tcritical (10.0353 > 2.0752). According to the criteria of the test, the result showed that there is significance difference to students' writing ability in writing narrative text through Exploration - Explanation - Expression (E3) method. It means that, Exploration - Explanation - Expression (E3) method is effective to improve students’ ability in writing narrative text.